Helping Future Schoolteachers Discover and Teach Soil: An Example of Project-Based Learning - Delphine Aran (Spanish Journal of Soil Science, 2024)
In addition to fundamental knowledge, the teaching provided at primary school develop children’s perceptions of the world, particularly that of the effects of human activities on the environment. However, despite its importance in these issues, soil is virtually absent from school curricula, and even more so from the training of future schoolteachers. In order to provide knowledge about soil and its crucial role in the challenges facing humanity, an educational project has been developed at the University of Lorraine for students on the multidisciplinary bachelor’s degree in teaching course during the past 5 years. Over fifty students follow traditional soil science courses and then use their knowledge in an active-learning setting. Within the framework of a project-based learning, they organize and carry out an activity session focusing on soil in a class of elementary school pupils, which is a kind of practice for their future teaching careers. The students follow the different stage in building their project. They design their workshop around a soil-linked theme of their choice, respecting the curriculum expectations. They establish a scientific approach to the chosen question and draw up the timetable for their activity, specifying the learning objectives and the resources to be used. They then carry out their activity session with a class at a partner school. The project is assessed on the basis of the students’ concrete achievements, as well as their effective analysis of their work. This type of project-based teaching engages students because it gives them the opportunity to take ownership of the discipline through the production of a tangible output. Building and then carrying out the activity session helps to develop students’ independence, creativity, and teamwork while at the same time imposing a framework that they must respect. It also enabled them to create a good quality animation, even though for most of them this was their first introduction to the subject of soils.